2021
DOI: 10.1037/ppm0000272
|View full text |Cite
|
Sign up to set email alerts
|

“Get out of my selfie!” Narcissism, gender, and motives for self-photography among emerging adults.

Abstract: Emerging adults, defined as individuals between the ages of 18 and 29, are the most common users of social media. In addition, more than half of emerging adults have shared a "selfie," or a photograph taken of oneself, on social media. Selfies have been linked to various aspects of narcissism, though there is some evidence that this may vary by gender and age. The present study aimed to unpack links between gender, narcissism, and selfie-taking behaviors and to document motives for taking selfies. A total of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Kapidzic (2013) has found that narcissism is a strong predictor of selfie-posting behavior. A narcissist is more likely to share selfies on social networking sites than others (Wang et al, 2012).A sample of 276 college students confirmed that grandiose and exhibitionistic forms of narcissism are significant predictors of selfie-posting behavior (Koterba et al, 2021).…”
Section: Narcissism and Selfie-posting Behaviormentioning
confidence: 87%
“…Kapidzic (2013) has found that narcissism is a strong predictor of selfie-posting behavior. A narcissist is more likely to share selfies on social networking sites than others (Wang et al, 2012).A sample of 276 college students confirmed that grandiose and exhibitionistic forms of narcissism are significant predictors of selfie-posting behavior (Koterba et al, 2021).…”
Section: Narcissism and Selfie-posting Behaviormentioning
confidence: 87%
“…Females are more likely to take personal and group sel es, post personal sel es, crop photos and use photographic lters as compared to male counterparts (51). Though no gender difference emerged from sel es taken alone (52), sel es featuring others were more common among females (53). Sel e posting among females show a stronger association with leadership and/or authority, while male's use of sel e seems to be linked to ideas of entitlement and exploitation (54).…”
Section: Gender Differences In Hvsm Usementioning
confidence: 97%
“… Kaurin et al (2018) coded the recent selfies uploaded on social media and found that extraversion was positively associated with selfies with a pet. In addition, research has shown a connection between narcissistic personality and selfies (e.g., Shane-Simpson et al, 2020 ; Wang et al, 2020 ; Koterba et al, 2021 ). For example, Wang et al (2020) found that narcissistic individuals are more likely to post their selfies on social media because they are satisfied with their bodies.…”
Section: Background Researchmentioning
confidence: 99%